2020
DOI: 10.1371/journal.pone.0236249
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome sequencing of Coccinella septempunctata adults (Coleoptera: Coccinellidae) feeding on artificial diet and Aphis craccivora

Abstract: Background The insect predator Coccinella septempunctata can effectively control many types of pests, such as aphids, whiteflies, and small lepidopteran larvae. We previously found that C . septempunctata fed an artificial diet showed diminished biological properties(e.g. fecundity, egg hatching rate, survival rate, etc.) compared with those fed natural prey ( Aphis craccivora ), likely due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…After consuming an artificial diet, egg production and hatching rates decrease in C. septempunctata , which restricts large-scale production of lady beetle. Using transcriptome sequencing, our research team demonstrated that the expression of the JH receptor Met was downregulated in C. septempunctata fed on an artificial diet ( Cheng et al 2020a ). We speculated that the decline in egg production and hatching rates of C. septempunctata reared on artificial diets may be caused by downregulation of Met expression.…”
Section: Introductionmentioning
confidence: 99%
“…After consuming an artificial diet, egg production and hatching rates decrease in C. septempunctata , which restricts large-scale production of lady beetle. Using transcriptome sequencing, our research team demonstrated that the expression of the JH receptor Met was downregulated in C. septempunctata fed on an artificial diet ( Cheng et al 2020a ). We speculated that the decline in egg production and hatching rates of C. septempunctata reared on artificial diets may be caused by downregulation of Met expression.…”
Section: Introductionmentioning
confidence: 99%
“…The seven-spot ladybird, Coccinella septempunctata L. (Coleoptera: Coccinellidae), is as an important natural predator of many insect pests and has the advantages of ecological adaptability and plasticity [2,3]. Extensive research has been conducted on C. septempunctata to investigate artificial diets, biological characteristics, predation response, and artificial propagation [4][5][6][7][8]. The bean aphid (Aphis craccivora Koch) is a cosmopolitan pest with a high reproductive rate and short life cycle, enabling outbreaks and virus transmission among plants.…”
Section: Introductionmentioning
confidence: 99%
“…We previously compared the nutritional composition of basic artificial diets with the Aphis craccivora diet and found that the fat and sugar content in the artificial diet was lower than A. craccivora , whereas the protein and amino acid content in the artificial diet was higher than A. craccivora ( Cheng 2018 ). However, transcriptomic analysis of C. septempunctata fed on the artificial diet revealed that differentially expressed genes in amino acid metabolism were generally downregulated, indicating that the absorption and utilization of proteins and amino acids in the artificial diet was poor, thus impacting growth and development ( Cheng et al 2020 ). Consequently, it is critical to consider the conversion and utilization of dietary ingredients by ladybugs and include natural compounds that are nutrient-rich.…”
mentioning
confidence: 99%